2003
DOI: 10.1152/ajpregu.00325.2002
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic and metabolic response to glucagon in fasting king penguins: phase II vs. phase III

Abstract: This study aims to determine how glucagon intervenes in the regulation of fuel metabolism, especially lipolysis, at two stages of a spontaneous long-term fast characterized by marked differences in lipid and protein availability and/or utilization (phases II and III). Changes in the plasma concentration of various metabolites and hormones, and in lipolytic fluxes as determined by continuous infusion of [2-3 H]-glycerol and [1-14 C]palmitate, were examined in vivo in a subantarctic bird (king penguin) before, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…R a glycerol is recognized as the best estimate of lipolysis, and it has been widely used to quantify whole-body lipolytic rates in vertebrates, including mammals Wolfe, 1992;Weber et al, 1993;McClelland et al, 2001;Henderson et al, 2007;Houser et al, 2007), birds (Bernard et al, 2002;Bernard et al, 2003;Vaillancourt and Weber, 2007) and fish (Bernard et al, 1999). Using R a glycerol for this purpose is recommended because the glycerol produced by lipolysis must obligatorily appear in the circulation, in situ recycling being prevented by the negligible activities of glycerol kinase in the adipose tissue and muscle of vertebrates (Newsholme and Taylor, 1969;Brooks et al, 1982;Reshef et al, 2003).…”
Section: Assessing Lipolytic Rate and Reesterification In Vivomentioning
confidence: 99%
“…R a glycerol is recognized as the best estimate of lipolysis, and it has been widely used to quantify whole-body lipolytic rates in vertebrates, including mammals Wolfe, 1992;Weber et al, 1993;McClelland et al, 2001;Henderson et al, 2007;Houser et al, 2007), birds (Bernard et al, 2002;Bernard et al, 2003;Vaillancourt and Weber, 2007) and fish (Bernard et al, 1999). Using R a glycerol for this purpose is recommended because the glycerol produced by lipolysis must obligatorily appear in the circulation, in situ recycling being prevented by the negligible activities of glycerol kinase in the adipose tissue and muscle of vertebrates (Newsholme and Taylor, 1969;Brooks et al, 1982;Reshef et al, 2003).…”
Section: Assessing Lipolytic Rate and Reesterification In Vivomentioning
confidence: 99%
“…A priming dose of labelled glycerol equivalent to 30·min of infusion was administered before starting the actual infusion. This protocol ensured that isotopic steady state was reached in less than 40·min (Bernard et al, 2002a;Bernard et al, 2003). Blood samples (450·l each) were drawn from the arterial catheter 50 and 60·min after starting the infusion to determine glycerol kinetics under thermoneutral conditions (22°C).…”
Section: Glycerol Kineticsmentioning
confidence: 99%
“…Overall, body size effects on metabolic rate can only explain <50% of these large differences [calculated using the classic allometric equation for resting mammals (Schmidt-Nielsen, 1990)]. Lipolytic rate is also one order of magnitude higher in sandpipers than in king penguins (Bernard et al, 2002a;Bernard et al, 2002b;Bernard et al, 2003), the only other avian species measured to date. In addition, it is clear that the values of R a glycerol reported here lie at the lower end of the range of lipolytic rates achievable by ruff sandpipers for several reasons: (1) migration flights would simply not be possible without activating lipolysis well beyond the rates measured in this study (see next paragraph); (2) the animals used here were not physiologically prepared for migration (Vaillancourt et al, 2005) and they were not acclimated to hypoxia (a treatment known to stimulate lipolytic rate) (McClelland et al, 2001); (3) ruff sandpipers were measured here only 1-5·h after the cessation of feeding whereas all the mammalian species mentioned in Fig.·5 for comparison were fasted for much longer durations (18-24·h); and (4) it has been suggested that incomplete hydrolysis of triacylglycerol may take place in bird adipose tissue (Goodridge and Ball, 1965), and significant production of mono-and diacylglycerol in bird adipocytes would make R a glycerol underestimate true lipolytic rate (a situation that does not exist in mammals) (Brooks et al, 1982).…”
Section: Unusually High Lipolytic Rates In Migrant Birdsmentioning
confidence: 99%
See 2 more Smart Citations